PENGEMBANGAN RUMUS KORELASI CLEGG IMPACT VALUE DAN NILAI CALIFORNIA BEARING RATIO PADA TANAH KELANAUAN UNTUK TIMBUNAN - Frengki Ashari Aritonang; Muhamad Yusa; Ferry Fatnanta (Racic : Rab Construction Research, 2025)
In embankment construction, material selection is critical and must meet technical requirements to ensure quality and safety. The California Bearing Ratio (CBR) value is commonly used to determine the soil bearing capacity in supporting loads applied above it. However, field CBR testing is relatively time-consuming, especially for large- scale projects. Therefore, a faster yet accurate alternative testing method is needed. One such alternative is the use of the Clegg Impact Hammer (CIH). This study aims to analyze and develop a correlation formula between the Clegg Impact Value (CIV) and field CBR values, using the Dynamic Cone Penetrometer (DCP) on ML (silt) and MH (elastic silt) soils for embankment construction. The research was conducted in Pomalaa, Southeast Sulawesi through field testing and laboratory testing (soil physical properties). Field tests included DCP and CIH, while laboratory tests covered moisture content and Atterberg limits. The results showed that the silty soils had a moisture content ranging 13.11%-46.95%, liquid limit 32.65%-90.09%, plastic limit 26.62%-59.26%, and plasticity index 5.53%- 33.63%. Field testing (DCP and CIH) showed the best correlation in MH soil at a depth of 20 cm, with an R² value of 0.6979. The resulting correlation formula is %CBR= 0.5896(CIV)1.02. With a correlation coefficient categorized as “strong,” this correlation has the potential to be used as a rapid method for determining CBR values in the field.